(untitled) (International Journal of Nursing Education, 2021)
A descriptive study carried out the knowledge regarding staff development programme importancein nursing among female staff nurses working in tertiary care centre, Chennai -03. The knowledgewas assessed using structured knowledge questionnaires. The data analysis, among the 30 staff nurseslevel of knowledge of SDP importance in nursing according to their knowledge assessed by using selfstructured questionnaire 16% of female staff nurses having inadequate knowledge, 22 % of the femalestaff nurses having moderate knowledge, 62 % of the female staff nurses having adequate knowledge.